Mata Sebagai Objek dalam Karya Seni Grafis - Yusandi Yusandi; Ariusmedi Ariusmedi (Journal on Education, 2023)
The purpose of creating this work is to visualize the Eye as an Object in a Graphic Art Work. The eye is a sensory organ that helps humans in everyday life whose function is to see, besides that the eye is also able to communicate feelings that we feel such as feelings of sadness, happiness, fear and anger, all of which can be seen from the reaction of the eyes as a real picture of the feelings we feel. communicated by the eye, this is what makes the idea of creation and the subject matter for the writer to produce a graphic art work with the cut out stencil print technique. This work also aims to introduce eye reactions as a symbol of human feelings from the description of social events that seen in everyday life. The method applied to making this final work goes through stages including Preparation, Elaboration, Synthesis, Concept Realization, and finally the completion stage. In the Graphic Art works that the author created, there are 10 works with the title; Flood Tears, Dice and Snakes and Ladders, Help, Cracked And Broken, 5 Times, mato suntiang, Threatened, Bullying, Maliek anak, Behind the hole.